RESPONS TANAMAN KEDELAI TERHADAP INTERVAL PEMBERIAN AIR DAN SERBUK GERGAJI - Mukhsin, Mukhsin; Setyaji , Hajar (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2026)
Soybeans are classified as plants that are not resistant to drought and excess water. Lack of water will reduce yields, while excess water will cause damage to the roots, thus disrupting growth and reducing yields. In this regard, it is necessary to provide proper water, in addition to that, so that the water provided can be retained in the soil, it is necessary to add sawdust. The study aimed to determine the response of soybean plants to the interval of watering and sawdust was carried out at the Teaching and Research Farm, Faculty of Agriculture, Jambi University. The research design used was a Completely Randomized Design with a factorial pattern. The first factor was the watering interval (A) which consisted of 3 levels, namely: a1: once a day, a2: once every 3 days and a3: once every 5 days. The second factor was Sawdust (S) which consisted of 3 levels, namely: s1: 0% of the media weight, s1: 2.5% of the media weight s3: 5% of the media weight. The results showed that there were differences in the response of soybean plants that were given water once every 1, 3 and 5 days on media given sawdust. The observed variables include: Watering once every three days in a planting medium containing 2.5% sawdust resulted in the best growth with a seed weight of 25.94 grams per plant.